Factors influencing optimum countermovement jump performance and movement strategy in championship professional football players: implications for player profiling - Mitchell, A.; Holding, C.; Greig, M. (Research in Sports Medicine, 2022)
Single leg countermovement jump (CMJ) is a common profiling test influenced by sport, age, sex and playing level. Controlling for these confounding variables, outfield players from an English Championship squad (n=36) were retrospectively categorized as best (n=10) or worst (n=10), based on mean single leg CMJ height and flight time:contraction time ratio. Movement strategy was quantified as force-time history metrics differentiating eccentric and concentric phases. Jump height revealed that best performers elicited greater rate of force development in both phases (P=0.033), with concentric impulse the strongest predictor of performance. Time ratio also differentiated best performers as utilizing a shallower (P=0.002) countermovement, with concentric rate of force development the strongest predictor of good performance. Successful jump height performance can mask ineffectual eccentric and stretch shortening cycle neuromuscular characteristics. Time ratio is therefore advocated as the key performance indicator, with movement strategy prioritized over gross outcome measures.